Reirradiation for Sinonasal Adenoid Cystic Carcinoma in a Low-Middle Income Setting: A Case Report and Literature Review - Kaabia, Wael; Mousli, Alia; Attia, Najla; Naija, Bouchra; Ghorbel, Asma; Ben Zid, Khadija; Zarraa, Semia; Abidi, Rim; Nasr, Chiraz (Case reports in oncology, 2025)
Introduction: Reirradiation for recurrent adenoid cystic carcinoma (ACC) of the head and neck poses significant clinical challenges, particularly in low- and middle-income countries where access to advanced radiation modalities such as proton or carbon ion therapy is limited. Given the tumor’s radioresistant nature and the risk of cumulative toxicity to critical structures, reporting experiences with accessible and precise photon-based techniques remains essential. This case highlights the potential of volumetric modulated arc therapy (VMAT) as a feasible reirradiation option in such settings. Case presentation: We report the case of a 79-year-old male with a history of left ethmoidal sinus ACC initially treated with surgery followed by cobalt-based radiotherapy. Eighteen years later, the patient presented with an inoperable local recurrence. A multidisciplinary tumor board recommended reirradiation using VMAT. A total dose of 60 Gy in 30 fractions was delivered, with careful dosimetric planning to respect cumulative tolerance thresholds of organs at risk. The treatment was well-tolerated, with no acute grade ≥3 toxicities. Post-treatment imaging showed a marked reduction in tumor volume, and the patient had no severe late toxicity during follow-up nor distant metastasis. Conclusions: This case illustrates the potential role of VMAT as a viable reirradiation strategy for head and neck ACC, particularly in resource-limited settings. It emphasizes the importance of individualized treatment planning, accurate dose delivery, and multidisciplinary evaluation in achieving tumor control while minimizing toxicity. Such experiences contribute valuable insights into the management of complex recurrent tumors where therapeutic options are limited.